Joint Analysis of Functional and Structural Connectomes Between Preterm and Term Infant Brains via Canonical Correlation Analysis With Locality Preserving Projection - Zhang, Shu; He, Zhibin; Du, Lei; Zhang, Yin; Yu, Sigang; Wang, Ruoyang; Hu, Xintao; Jiang, Xi; Zhang, Tuo (Frontiers in Neuroscience, 2021)
Preterm is a world-wide problem which affects infants’ lives significantly. Moreover, the early impairment is more than limited to isolated brain regions but global and profound to introduce negative later outcome, such as cognitive disorder. Therefore, seeking the differences of brain connectome between preterm and term infant brains is a vital step for understanding the developmental impairment caused by preterm. Existing studies revealed that studying the relationship between brain function and structure, and further investigating their differentiable connectomes between preterm and term infant brains is a way to comprehend and unveil the differences occurred in the preterm infant brains. Therefore, in this paper, we proposed a novel Canonical Correlation Analysis (CCA) with Locality Preserving Projection (LPP) approach to investigate the relationship between brain functional and structural connectomes and how such a relation differs between preterm and term infant brains. CCA is proposed to study the relationship between functional and structural connections, while LPP is adopted to identify the distinguishing features from the connections which can differentiate the preterm and term brains. We successfully identified 89 functional and 97 structural connections which mostly contributed to differentiate preterm and term infant brains from the fMRI and dMRI of the public developing Human Connectome Project (dHCP) dataset. By further exploring those identified connections, the results revealed that the functional connections are short-range and within the functional network. On the contrary, the identified structural connections are usually remote connections across different functional networks. These connectome-level results suggest that longitudinal functional changes could deviate from longitudinal structural changes in the preterm infant brains, which help better understand the brain-behavior changes in preterm infant brains.